The competences of European Union institutions in the trade policy (Lisbon Treaty) - Timbur, Margareta (Studies and Scientific Researches. Economics Edition, 2010)
The European Union is the best known at the world’s leading trade power and the common trade policy is the core of EU external relations. The events of the last years and the extension of the EU to 27 member proved that the functioning system could no longer continue and was requiring a new institutional framework. The Lisbon Treaty was the right solution. It purposes are to bring changes for the citizens, institutions, external relations foe the consolidation of democracy in EU. This paper attempts to provide an overview of the major revisions introduced by the Treaty of Lisbon regarding the trade policy. Also, it analyses the extension and clarification of EU competence, the greater role of the European Parliament and the inclusion of investment policy in trade policy, the voting rules in trade area and the international negotiation of trade agreements. The study describes, as well, the impact of Lisbon Treaty implementation on the MS which are independent nations, but without power of decision in the common trade policy.